CRIMINALIZATION OF TERRORISM IN LITHUANIA - Pakštaitis, Laurynas (Teisė, 2016)
The article presents analysis of modern trends of criminalization of terrorism crimes in the Criminal Code of Lithuania. The amendments to the Criminal Code (CC) of July 2nd of 2013 introduced new definition of an act of terror (art. 250 of the CC). New crimes of creation of groups for the commission of terrorist crimes (art. 2491 of the CC), incitement of terrorist crimes (art. 2501 of the CC), recruitment for terrorist activities (art. 2502 of the CC), threats to commit a terrorist crimes (art. 2503 of the CC), financing and support for terrorist activities (art. 2504 of the CC), training of terrorists (art. 2505 of the CC), new wording of a crime of hijacking of an aircraft, ship or other type of public or transportation vehicle or stationary platform on shelf (art. 251 of the CC) has been provided as well as definitions of ‘terrorist crimes’, ‘crimes related to the terrorist activities’, ‘terrorist aims’ were presented (art. 2521of the CC). Such criminalization was based on the Council Framework Decision of 13 June 2002 on combating terrorism (2002/475/JHA) and was a major breakthrough for the criminal law of Lithuania. The definitions of modern terrorism which date back to the CC of 1961 were lacking the features of the phenomenon. Particularly the features of mens rea i.e. terrorist objectives, aims and motives were lacking. The new CC of 2000 provided inaccurate and unmotivated definition of an act of terror which opened grounds for unspecific violent crimes to be defined as terrorism. In the article problems of various definitions of terrorism are discussed with an objective to find appropriate ground for the accurate wordings of an act of terror in the CC. The essence of terror and criterions for criminalization are discussed. The analyzed changes of the terrorism definitions in the Criminal Code made Lithuanian legislation against terrorism completely in tune with international instruments and provided a well grounded wording for the practitioners. Even though the definition of an act of terror in the main norm of the CC incorporates acts directly not related to terror, specific aim to act with terrorist objectives provided a well-founded definition. International trends of widening the norms and implementing wide approach to enable state authorities in fight with terrorism crimes are analyzed. The hazards of extra-wide criminalization are mentioned. Special emphasis is laid on the analysis of terrorist objectives and the definitions of terrorist aims provided in the Criminal Code.